Study on multi-scenario and multi-water source allocation in Henan water supply area of Yellow River considering extreme drought - Zheng, Xiaokang; Wang, Weihao; Wang, Yu; Ma, Chao; Wan, Fang (Frontiers in Environmental Science, 2025)
The water supply of water resources allocation under extreme drought is insufficient, and the limited available water resources make it urgent to tap the potential of water supply. In this study, the Yellow River water supply area in Henan Province is taken as an example to study the multi-water source allocation under extreme drought. According to the Palmer Drought Severity Index (PDSI), the extreme drought years are selected, and the water supply and demand balance in the extreme drought years is analyzed, and the water shortage degree of each water supply area is obtained. In this study, unconventional water, flood resource utilization and elastic exploitation of groundwater are used as potential water sources. Different water supply scenarios are set up according to different potential tapping measures, and multi-scenario supply increase under extreme drought is explored. In the case of severe drought, the amount of potential tapping water has been significantly improved through different scenarios of potential tapping measures. The amount of potential tapping water in the three scenarios is 1.499 hundred million m3, 2.745 hundred million m3 and 3.991 hundred million m3. Under different water supply scenarios, the total water shortage has been reduced from 4.555 hundred million m3 to 3.054 hundred million m3, 1.808 hundred million m3 and 0.562 hundred million m3, respectively. The total water shortage rate decreased from 31.07% to 20.83%, 12.33% and 3.83%, respectively. A multi-water source allocation model with the goal of minimizing water shortage is constructed, and a multi-scenario supply increase allocation scheme is proposed, which provides a basis for the study of water supply increase allocation to alleviate the drought degree of the Yellow River Water Supply Area in Henan. Through the Multi-scenario potential tapping of multiple water sources, the existing potential water volume can be maximized, which is conducive to reducing the water supply pressure and water use restrictions of conventional water sources, improving the support capacity and guarantee capacity of water resources, and reducing the economic and social development bottlenecks caused by extreme drought.